Designing of optical laser and spectral equipment for research and educational applications, development of new materials and technologies at the laser physics and spectroscopy department of the Belarusian State University - Voropay, Eugeni S.; Gulis, Igor M.; Melnikova, Elena A.; Tolstik, Alexei L. (Journal of the Belarusian State University. Physics, 2019)
This paper presents the main developments in the field of optical laser instrument making, the achievements in the creation of new materials and technologies realized at the laser physics and spectroscopy department within the scope of the state financed research and engineering programs. Some developments have been realized with the colleagues from other divisions of BSU and from other research organizations. The developments include a pulsed spectrofluorimeter for kinetic studies in the nanosecond range; modular spectrometric system for educational and research applications (recording of absorption, emission, and Raman spectra); hyperspectrometer offering recording of luminescence spectra from numerous points of the object; video microspectrometric system for analysis of the spectral characteristics of extended objects; hardware and software for digital diagnostics enabling assessment of the holographic protective elements used at securities and documents; identifier of diffraction structures with the coding elements which combine the principles of holo graphic protection and bar coding; several laboratory complexes for practical training: in laser physics - based on an yttrium aluminum garnet laser and on lasers with frequency-tunable generation enabling studies of different dynamic modes and methods for the wave tuning; in coherent optics and holography - for recording of phase holograms with the use of diode-pumped lasers; in fiber-optical data processing and transmission; in micro- and nanophotonics. A new-generation photosensitizer for photodynamic therapy of oncologic diseases has been developed on the basis of polymethine dyes; the photoactivated antimicrobial compounds for therapy of infectious diseases have been proposed. A submicron-resolution technology for layer-by-layer analysis of protective and functional coatings has been developed; a technology to produce protective elements for debenture papers has been proposed.
Keywords: laser physics; spectroscopy; holography; fiber-optical systems; spectrometers; hyperspectroscopy; protection of securities; photosensitizer